Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Step-by-step explanation:
[tex]\\ \tt{:}\leadsto \frac{2 - 3x}{4 - 8} = \frac{3x}{4} \\ \\ \tt{:}\leadsto 4(2 - 3x) = 3x(4 - 8) \\ \\ \tt{:}\leadsto 8 - 12x = 3x( - 4) \\ \\ \tt{:}\leadsto 8 - 2x = - 12x \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \tt{:}\leadsto 8 = - 12x + 2x \\ \\ \tt{:}\leadsto 8 = - 10x \\ \\ \tt{:}\leadsto x = \frac{ - 10}{8} \\ \\ \tt{:}\leadsto x = \frac{ - 5}{4} [/tex]
Answer:
x=-1
Step-by-step explanation:
2-3x/4-8=3x/4
bring all variables to one sides and the non variable to the other
-3x/4-3x/4=-2+8
Simplify
-3x/2=6
Bring 2 to the other side
-3x= 6/2
-3x=3
Bring -3 to the other side
x=3/-3
x=-1
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.